Estimation of endotracheal tube cuff pressure among anaesthesia providers does experience matter? - Raha AR,; Haslinda S,; Nadia MN,; Nurlia Y, (Department of Surgery, UKM Medical Centre, 2011)
The endotracheal tube (ETT) cuff pressure is usually estimated and assumed to be within the appropriate range. However, the estimation of cuff pressure may be influenced by the various estimation techniques used by anaesthesia providers and their different experience level. The main aim of this study was to observe the correlation between the experience of the anaesthesia providers and their ability to estimate endotracheal cuff pressure in a correct manner. One hundred anaesthesia providers were classified into three different groups based on their months of anaesthetic experience: Group I (< 36 months), Group II (36 to 59 months) and Group III (≥ 60 months). Following intubation, the ETT cuff was inflated by the anaesthetic nurse and ETT placement verified by the anaesthesia provider. Using the pilot balloon palpation technique (PBPT), the cuff pressure was estimated to be within the appropriate pressure range, over or under-inflated. The necessary adjustments were made if needed after measurement with a VBM™ Manometer Pressure Gauge. More number of months of anaesthesia experience was not associated with a greater ability to correctly estimate the ETT cuff pressure. However, this correlation was poor (r = - 0.177). The pilot balloon palpation technique was found to be only moderately sensitive (76.5%) but poorly specific (42.9%) for correct estimation of the ETT cuff pressure, whereby PPV and NPV were 58.2% and 63.6%, respectively. The technique was 50% (95% CI 24.04 - 75.95) sensitive while correctly estimating the under-inflated cuff and 60% (95%CI 13.25-37.81) sensitive to correctly estimating the over-inflated cuff. The results depict that the experience of anaesthesia providers did not correlate with the ability to correctly estimate the ETT cuff pressure